2017
DOI: 10.1017/s1355617717000534
|View full text |Cite
|
Sign up to set email alerts
|

Lutein and Zeaxanthin Influence Brain Function in Older Adults: A Randomized Controlled Trial

Abstract: L and Z supplementation appears to benefit neurocognitive function by enhancing cerebral perfusion, even if consumed for a discrete period of time in late life. (JINS, 2018, 24, 77-90).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 88 publications
4
69
0
Order By: Relevance
“…The brain, like the retina, is highly vascularized and lutein, either localized in cells or circulation, might be expected to affect that vasculature. Recent research using the same participants as tested in this study suggests that supplementing L and Z can also change cortical blood flow, measured during a word recall test in an fMRI testing environment, which would be consistent with vascular effects.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The brain, like the retina, is highly vascularized and lutein, either localized in cells or circulation, might be expected to affect that vasculature. Recent research using the same participants as tested in this study suggests that supplementing L and Z can also change cortical blood flow, measured during a word recall test in an fMRI testing environment, which would be consistent with vascular effects.…”
Section: Discussionsupporting
confidence: 75%
“…As part of a larger study on MPOD and cognitive and neurological function, data from 85 right‐handed community‐dwelling adults were analyzed in this sub‐study. The young adult study group ( n = 43) was composed of male and female participants aged 18–30 years ( M = 20.79 ± 2.16 years; 46.5 % female).…”
Section: Methodsmentioning
confidence: 99%
“…Healthrelated benefits associated with a high carotenoid intake include enhanced immune system functions and lower risk of developing degenerative chronic diseases, such as age-related macular degeneration, type 2 diabetes, obesity, certain types of cancer (breast, cervical, ovarian, colorectal), and cardiovascular diseases, among others [301][302][303][304][305][306][307][308]. Carotenoids are also attracting interest as promoters of cognitive functions [309][310][311] as well as skin photoprotectants and providers of cosmetic benefits, particularly in the context of the rapidly expanding nutricosmetics area [312]. Because carotenoids may undergo significant degradation and/or metabolism in the human body, it is far from certain whether the native compounds or rather their metabolites are responsible for the attributed health effects.…”
Section: Health Benefitsmentioning
confidence: 99%
“…There is evidence of a protective role of lutein and zeaxanthin against age-related macular degeneration, a major cause of blindness in the elderly [326,328,331,332]. Moreover, they also accumulate in brain tissue and there is increasing evidence that they provide cognitive benefits [309][310][311].…”
Section: Health Benefitsmentioning
confidence: 99%
“…A number of recent studies have shown that lutein status (i.e., measured in serum/diet and directly in retina, MP) correlates with a number of centrally‐mediated functions including numerous aspects of cognition . In addition, recent imaging studies also suggest a relationship between lutein and CNS functioning …”
Section: Introductionmentioning
confidence: 99%